Human Antibody Responses Following Vaccinia Immunization Using Protein Microarrays and Correlation With Cell-Mediated Immunity and Antibody-Dependent Cellular Cytotoxicity Responses. (1st March 2021) - Frey, Sharon E; Stapleton, Jack T; Ballas, Zuhair K; Rasmussen, Wendy L; Kaufman, Thomas M; Blevins, Tammy P; Jensen, Travis L; Davies, D Huw; Tary-Lehmann, Magdalena; Chaplin, Paul; Hill, Heather; Goll, Johannes B; et al.
Abstract: Background: There are limited data regarding immunological correlates of protection for the modified vaccinia Ankara (MVA) smallpox vaccine. Methods: A total of 523 vaccinia-naive subjects were randomized to receive 2 vaccine doses, as lyophilized MVA given subcutaneously, liquid MVA given subcutaneously (liquid-SC group), or liquid MVA given intradermally (liquid-ID group) 28 days apart. For a subset of subjects, antibody-dependent cellular cytotoxicity (ADCC), interferon-γ release enzyme-linked immunospot (ELISPOT), and protein microarray antibody-binding assays were conducted. Protein microarray responses were assessed for correlations with plaque reduction neutralization titer (PRNT), enzyme-linked immunosorbent assay, ADCC, and ELISPOT results. Results: MVA elicited significant microarray antibody responses to 15 of 224 antigens, mostly virion membrane proteins, at day 28 or 42, particularly WR113/D8L and WR101H3L. In the liquid-SC group, responses to 9 antigens, including WR113/D8L and WR101/H3L, correlated with PRNT results. Three were correlated in the liquid-ID group. No significant correlations were observed with ELISPOT responses. In the liquid-ID group, WR052/F13L, a membrane glycoprotein, correlated with ADCC responses. Conclusions: MVA elicited antibodies to 15 vaccinia strain antigens representing virion membrane. Antibody responses to 2 proteins strongly increased and significantly correlated with increases in PRNT. Responses to these proteins are potential correlates of protection and may serve as immunogens for future vaccine development. Clinical Trials Registration: NCT00914732. Abstract : Protein microarray responses were assessed for correlations with antibody and cellular immune results. Modified vaccinia Ankara elicited antibodies to 15 Western Reserve proteins; 2 proteins were significantly correlated with increases in neutralizing antibody and may serve as immunogens for future vaccine development.